Food Commerce Upshots With Their Former Locus In The Economy With Respect To The Pandemic 2020 - A Drawback Or An Aid In South Kolkata, West Bengal ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: The Food Commerce industry has flourished massively during the past decade  in South Kolkata in West Bengal, with new outlets opening every now and then, so much so  that this region is known as ‘Food Street’. Regardless of their scale of operations, each of  these outlets had well established themselves, catering to their respective target markets and  earning decent amount of revenue over the years. However, this growth suffered a setback  owing to the origin of novel Coronavirus SARS-n-CoV-2. The growth rate declined to a great  extent over the span of two years, with recent studies showing an overall stunted growth rate.  Even though online marketing of these outlets and selling the food through delivery apps have  aided the entrepreneurs, the cost to revenue ratio is not at par with that of the times before  the pandemic hit. Overall, the pandemic has impacted the eateries in more way than initially  imagined. Objectives: a) To reveal the various problems and scenarios of managing food  business during the Covid-19 pandemic in South Kolkata region; b) To compare the present  scenario of the food industry with how things were before prior to the pandemic to understand  the nature of change during this time frame; and, c) To describe the challenges and methods  implemented by the food retail business entrepreneurs and managers of the randomly selected  establishments to hold a steady business flow during the Covid-19 pandemic. Methodology:  The study follows a descriptive research design. Therefore, the research will describe the  characteristics of the sample under study. The food outlets of South Kolkata have been chosen  as the study location. 100 respondents were selected. The respondents are those who consume  food from these outlets such that they represent the wider target market of the ‘Food Street’.  Both Primary Data and Secondary Data were used. Primary Data was collected through  sample survey. Random Sampling technique was used to choose the respondents. The study  used quantitative data, therefore, only Quantitative analysis was performed. Results: The  Research was able to depict the comparison between the present scenario and the situation  prior to the pandemic. The study was able to reveal the challenges and problems that the food  outlets had to suffer from. Also, the methods or strategies taken up by the entrepreneurs of these outlets to overcome the pandemic were discovered. 46% of the respondents opted for  “Mobile Food Delivery” as their strategy to revive from losses. Conclusion: With COVID-19  having altered – and still in the process of altering – the definition of “normal” across the  world, most industries are still scrambling to adjust. The effect on the restaurant industry  has been particularly dramatic. With restaurants and pubs closed for sit-down service, many  establishments are struggling to keep their heads above water. The food outlets located in  South Kolkata shares the same fate and the research is able to highlight this effectively.
Keywords: South Kolkata; Covid-19 Pandemic; Food Outlets; Recovery Strategy; Restaurants Pubs; Delivery Apps